Endoscopic stenting for malignant biliary obstruction is technically successful in patients with preexisting duodenal stents - Simoes, Priya K.; Schattner, Mark A.; Gerdes, Hans; Shah, Pari M.; Kurtz, Robert C.; Mendelsohn, Robin B. (Endoscopy International Open, 2022)
Background and study aims There are limited data on the success of endoscopic retrograde cholangiopancreatography (ERCP) in patients with malignant biliary and duodenal obstruction with a preexisting duodenal stent. The aim of this study was to evaluate patient and procedural outcomes of a cohort of patients with preexisting duodenal stents who underwent an attempt at ERCP for malignant biliary obstruction (MBO).Patients and methods This was a single-center retrospective study on consecutive patients with a preexisting duodenal stent who underwent attempted ERCP for MBO. Technical success was defined as successful cannulation of the common bile duct, with successful dilation and/or deployment of a biliary stent under fluoroscopy. Clinical success was defined as number of patients in the entire group who underwent ERCP successfully with resolution of symptoms.Results We identified 64 patients (73 % men, 74 % white, median age 62 years) with a preexisting duodenal stent who underwent 85 attempts at ERCP. ERCP was technically successful in 50 of 85 procedures (59 %). Overall ERCP was successful in 41 of 85 patients (48 %). ERCP was more likely to be successful in patients with Type 1 and 3 duodenal strictures than with Type 2 strictures (83 % and 92 % vs. 42 %, P < 0.01), in patients with a preexisting sphincterotomy (79% vs. 20 %, P = 0.01) or preexisting biliary stent (66 % vs. 34 %, P = 0.04). Adverse events included bleeding (n = 3), post-procedure fever (n = 3) and abdominal pain (n = 1).Conclusions Although biliary stenting via ERCP is often technically challenging in patients with a prior duodenal stent, it is a safe and effective method of biliary drainage. ERCP should be attempted in patients with Type 1 and 3 duodenal strictures, a prior sphincterotomy or an indwelling biliary stent.